Neurochemical and Behavioral Profiling in Male and Female Rats of the Psychedelic Agent 25I-NBOMe - Miliano, Cristina; Marti, Matteo; Pintori, Nicholas; Castelli, Maria Paola; Tirri, Micaela; Arfè, Raffaella; De Luca, Maria Antonietta (Frontiers in Pharmacology, 2019)
4-Iodo-2,5-dimethoxy-N-(2-methoxybenzyl)phenethylamine (25I-NBOMe), commonly called “N-Bomb,” is a synthetic phenethylamine with psychedelic and entactogenic effects; it was available on the Internet both as a legal alternative to lysergic acid diethylamide (LSD) and as a surrogate of 3,4-methylenedioxy-methamphetamine (MDMA), but now it has been scheduled among controlled substances. 25I-NBOMe acts as full agonist on serotonergic 5-HT2A receptors. Users are often unaware of ingesting fake LSD, and several cases of intoxication and fatalities have been reported. In humans, overdoses of “N-Bomb” can cause tachycardia, hypertension, seizures, and agitation. Preclinical studies have not yet widely investigated the rewarding properties and behavioral effects of this compound in both sexes. Therefore, by in vivo microdialysis, we evaluated the effects of 25I-NBOMe on dopaminergic (DA) and serotonergic (5-HT) transmissions in the nucleus accumbens (NAc) shell and core, and the medial prefrontal cortex (mPFC) of male and female rats. Moreover, we investigated the effect of 25I-NBOMe on sensorimotor modifications as well as body temperature, nociception, and startle/prepulse inhibition (PPI). We showed that administration of 25I-NBOMe affects DA transmission in the NAc shell in both sexes, although showing different patterns; moreover, this compound causes impaired visual responses in both sexes, whereas core temperature is heavily affected in females, and the highest dose tested exerts an analgesic effect prominent in male rats. Indeed, this drug is able to impair the startle amplitude with the same extent in both sexes and inhibits the PPI in male and female rats. Our study fills the gap of knowledge on the behavioral effects of 25I-NBOMe and the risks associated with its ingestion; it focuses the attention on sex differences that might be useful to understand the trend of consumption as well as to recognize and treat intoxication and overdose symptoms.